INVESTIGATING THE CONNECTION BETWEEN INVESTMENT INTENTIONS AND LAND STATUS: INVESTIGATING THE CONNECTION BETWEEN INVESTMENT INTENTIONS AND LAND STATUS - Atanasova, Simona; Kirilova, Krasimira (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
The subject of investigating the connection between investment intentions and land status is analyzing the main procedures for preparation, approval and implementation of development plans with the objective of changing the purpose designation of agricultural land into urbanized territory. By using a project for a Detailed Development Plans – Plan for Regulation and Construction, an examination is performed of the processes related to the preparation and coordination of the plan, including the change of purpose designation of the agricultural land into land for non-agricultural uses, in accordance with the legislation.